Investigating the moderating effects of age of joint venture in the relationship between relationship characteristics and degree of inter-firm technology transfer - Sazali Abdul Wahab; Raduan Che Rose; Suzana Idayu Wati Osman (2011)
The main objective of this paper is to empirically examine the moderating effect of age of joint venture in the relationships between relationship characteristics: relationship quality and mutual trust and two distinct dimensions of degrees of technology transfer: degrees of tacit and explicit knowledge within IJVs. Using the moderated multiple regression (MMR), the theoretical models and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). The results revealed that age of JVs has significantly affected the relationship between relationship characteristics (relationship quality and mutual trust) and degree of tacit knowledge; where the relationship was found stronger for young JVs than old JVs. However, age of JVs did not significantly moderate the relationship between relationship characteristics and degree of explicit knowledge. The study has bridged the literature gaps in such that it offers empirical evidence and new insights on the moderating effect of age of joint ventures in the relationships between relationship characteristics and two distinct degrees of technology transfer: degrees of tacit and explicit knowledge using the Malaysian sample.